The Australian Economy in 2020–21: The COVID‐19 Pandemic and Prospects for Economic Recovery. (11th January 2021) - Lim, Guay; Nguyen, Viet; Robinson, Tim; Tsiaplias, Sarantis; Wang, Jiao
Abstract: This article summarises developments in the Australian economy in 2020. It describes the economic growth and labour market ramifications associated with COVID‐19, and the fiscal and monetary policies implemented to help counter its effects. COVID‐19 has resulted in considerable slack in an economy that was weak pre‐pandemic. While current policies are appropriately focused on stimulating demand and supporting employment, existing challenges such as weak growth in productivity, gross domestic product and real wages are also likely to remain relevant post‐pandemic.